Mark’s Mothers and the Matronymic: Linking ‘The Son of Mary’ (Mk 6.3) to ‘The Daughter of Herodias’ (Mk 6.22) - LaValle Norman, Dawn (New Testament studies, 2025)
This article argues that Mark uses matronymics, that is, identifying someone by the name of their mother, to construct female communities that resist Jesus’ message. This happens precisely twice in the Gospel of Mark, at Mk 6.3 (Jesus ‘the son of Mary’) and at Mk 6.22 (‘the daughter of Herodias’). Through comparison with other Greek uses of the matronymic, I will show that both scenes draw on the link between matronymics and female lines of authority, but with slightly different valences. Mark 6.3 heightens the female context of the Nazareth speakers and the hometown resistance, while Mk 6.22 is more concerned to establish a competing line of authority to that of Jesus in the person of Herodias and her daughter. My argument complements previous research into the Markan characterisation of the positive portrayals of multiple unnamed women in Mark’s Gospel (e.g. the women with the flow of blood (Mk 5.25-34), the Syrophoenician woman (Mk 7.24-30), the poor widow (Mk 12.41-4) and the woman who anoints Jesus in Bethany (Mk 14.3-9)). Joining the negative named women to the positive unnamed women reveals a unique feminine pattern of Markan characterisation, with its own dynamics and inflections.